Determinan Nilai Ekspor Negara Kawasan Regional Comprehensive Economic Partnership (RCEP) - Olivia, Shakira; Yasa, I Nyoman Mahaendra (Jurnal Ilmiah Wahana Pendidikan, 2025)
International trade under the Regional Comprehensive Economic Partnership (RCEP) fosters greater maritime logistics connectivity among member countries. Improved sea route efficiency enhances cross-border trade by reducing costs and time. As trade volume continues to rise, RCEP plays a crucial role in boosting maritime logistics competitiveness in the Asia-Pacific. However, from 2009 to 2023, disparities in export value growth emerged among RCEP countries. Key contributing factors include port productivity, trade route connectivity, and exchange rates.This study analyzes the simultaneous and partial effects of these variables on export value and identifies the most dominant factor. Using secondary data from 14 RCEP countries (2009–2023) sourced from UNCTAD and WITS, the study employs panel data regression with the Fixed Effect Model (FEM). Classical assumption tests confirm model validity. Findings reveal that port productivity, trade route connectivity, and exchange rates significantly influence export value, both jointly and individually. Trade route connectivity is identified as the most dominant variable. The study implies that enhancing port productivity through infrastructure upgrades, operational efficiency, and service improvement can strengthen a country’s trade performance and position in the global supply chain.